Mewujudkan Kesejahteraan Petani: Studi Implementasi Program CSR PT. Pertamina (Persero) Fuel Terminal Rewulu Terhadap Kesejahteraan Petani - Zukhruf Arifin; Abdul Aziz; Putri Liiza Diana Manzil; Yolanita Zahara (UIN Siber Syekh Nurjati Cirebon, 2020)
Various sustainable development efforts have been carried out in Indonesia, as an increase in people's welfare. As one of the efforts to synergize with the government in sustainable development aimed at the welfare of farmers, the CSR of PT. Pertamina (Persero) Fuel Terminal Rewulu seeks to form a program called Community Food Security (JAPANGMAS). The research aims to describe the implementation of the JAPANGMAS program in encouraging the welfare of farmers and the community. This study uses a qualitative descriptive approach to produce reliable and valid data and information. The case study method in IBI research is explanatory research. Data collection techniques using interviews, observation and discussion. Data sources as key information were taken by snowball sampling method from the company, village government, and the community. Data were analyzed using interactive methods. The results showed that the implementation of CSR programs had been carried out by achieving several indicators of the success of community empowerment. Through the implementation or stages of realization in accordance with community empowerment. But the need for improvement in product socialization and marketing so that more people are known.